Azelastine and suplatast shorten the distribution half-life of IgE in rats - Kazuhiko Hanashiro; Yoshihiro Tokeshi; Toshiyuki Nakasone; Masanori Sunagawa; Mariko Nakamura; Tadayoshi Kosugi (Mediators of Inflammation)
We aim to clarify whether suplatast and azelastine (anti-allergic drugs) can shorten the half-life of immunoglobulin E (IgE) in the circulating blood. Thirty Wistar rats were divided into six groups. Distilled water or anti-allergic drugs were given orally for 6 days after the first sensitization. Two milligrams of monoclonal dinitrophenyl (DNP)-specific rat IgE was administered to the rats, which had been given suplatast or azelastine orally. The level of DNP-specific rat IgE in the serum was estimated by IgE-capture enzyme-linked immunosorbent assay, and the turnover of IgE was analyzed from its pharmacokinetic parameters. The elimination half-life of rat IgE was about 12 h irrespective of the sensitized state. The intercompartmental rate constants (Kct and Ktc) in the suplatast-administered or azelastine-administered group were larger than those of the distilled water-administered group under non-sensitized conditions. These findings suggested that the anti-allergic drugs used in the present study facilitated the excretion of IgE from the circulation in rats.